Das "strukturelle Defizit" in der österreichischen Budgetpolitik: Berechnungsprobleme, Revisionen und wirtschaftspolitische Relevanz - Heimberger, Philipp (Wirtschaft und Gesellschaft, 2016)
This paper analyzes the role of the „structural deficit“ in Austrian fiscal policy. In the EU’s fiscal regulation framework, the structural budget balance serves as a central control indicator for assessing the sustainability of public finances. The structural balance is an estimate that has been corrected for the effects of the business cycle and one-off effects on the headline fiscal balance. The size of the structural balance heavily depends on a macroeconomic model employed by the European Commission to estimate the so-called output gap, which is interpreted as a measure of whether an economy is overheated or underutilized. This paper discusses the most acute estimation problems: in times of high unemployment, these problems are shown to lead to systematic underestimation of the degree of slack in the Austrian economy, which implies overestimation of the structural deficit. Pro-cyclical fiscal consolidation pressure is the result of these estimation problems; and this decreases the leeway of fiscal policy-makers when it comes to pushing for public investments that could stimulate growth and employment.